STRATEGI KOMUNIKASI LMX TERHADAP KINERJA KARYAWAN UD. BANK JELANTAH BENGKULU - Doli Saputra Nasution; Eceh Trisna Ayuh (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze leadership communication strategies in improving employee performance at UD Bank Jelantah Bengkulu by incorporating the Leader–Member Exchange (LMX) perspective, which emphasizes the quality of relationships between leaders and employees. A qualitative descriptive approach is applied, with data collected through interviews, observations, and documentation.The findings reveal that leaders employ communication strategies that are effective, directive, and persuasive, delivered through face-to-face interactions, work briefings, coordination activities, as well as motivation and feedback. These practices not only enhance message clarity and shared understanding but also reflect the quality of LMX relationships, such as trust, support, and openness between leaders and employees.Furthermore, these strategies contribute to improved employee motivation, discipline, and productivity. Overall, the integration of effective communication and strong LMX relationships creates a supportive and motivating work environment that facilitates the achievement of organizational goals and enhances overall employee performance Keywords: Communication Strategy, Motivational Communication, Employee Performance